Efficacy and ethics of intensive predator management to save endangered caribou - Chris J. Johnson; Justina C. Ray; Martin‐Hugues St‐Laurent (Conservation Science and Practice, 2022)
Abstract Lethal population control has a history of application to wildlife management and conservation. There is debate about the efficacy of the practice, but more controversial is the ethical justification and methods of killing one species in favor of another. This is the situation facing the conservation of woodland caribou (Rangifer tarandus caribou) in Canada. Across multiple jurisdictions, large numbers of wolves (Canis lupus), and to a lesser extent bears (Ursus americanus) and coyotes (C. latrans), are killed through trapping, poisoning or aerial shooting to halt or reverse continued declines of woodland caribou. While there is evidence to support the effectiveness of predator management as a stop‐gap solution, questions remain about the extent to which this activity can make a meaningful contribution to long‐term recovery. Also, there are myriad ethical objections to the lethal removal of predators, even if that activity is in the name of conservation. Debates about predator management, just one of numerous invasive actions for maintaining caribou, are made even more complex by the conflation of ethics and efficacy. Ultimately, long‐term solutions for the recovery of caribou require governments to stop delaying difficult decisions that address the real causes of population decline, habitat change.